Structural and optical properties of a-C:H:O:Cl and a-C:H:Si:O:Cl films obtained by Plasma Enhanced Chemical Vapor Deposition - Fernandes, Isabela Cristina [UNESP]; Hadich, Tayan Vieira [UNESP]; Amorim, Milena Kowalczuk Manosso [UNESP]; Turri, Rafael Gustavo [UNESP]; Rangel, Elidiane C. [UNESP]; Dias da Silva, José Humberto [UNESP]; Durrant, Steven F. [UNESP] (Elsevier, 2018)
Amorphous hydrogenated oxygenated chlorinated carbon materials with and without silicon were produced by PECVD at deposition rates of up to 150 nm min−1. Surface roughness, morphology and contact angle were almost independent of the main system parameter, namely the partial pressure of CHCl3 in the plasma feed, CCl. Infrared reflection absorption spectroscopy (IRRAS) of the films revealed the presence of C=O and C=C bonding in all the chlorinated films. IRRAS spectra also showed the presence of C-Cl bonds in the most chlorinated a-C:H:O:Cl films. Hydration of Si-Cl to Si-OH occurs in the a-C:H:Si:O:Cl films. As revealed by Energy-dispersive X-ray spectroscopy (EDS) the Cl content increases and the O content decreases as CCl increases. Under the range of conditions used, [Cl] reached maxima of ∼32 at.% and 25 at.%, respectively, for the series of a-C:H:O:Cl and the a-C:H:Si:O:Cl films. For the a-C:H:Si:O:Cl films the Si content decreases with increasing CCl. Optical properties were calculated from Ultraviolet-visible near infrared spectral data. Refractive indices varied between ∼1.52 and 1.78, depending on CCl. The Tauc gaps can be selected by a suitable choice of CCl in the range of roughly 1.3–2.6 eV.
Keywords: Chlorinated plasma polymers; Optical properties; PECVD; Ultraviolet-visible near infrared spectroscopy